Signing of Grant Agreement with Mozambique: Contributing to the improvement of people’s living environment in Niassa Province through the construction of a rural water supply facility - JICA (2021)
On February 26, 2021, the Japan International Cooperation Agency (JICA) signed a grant agreement with the Government of the Republic of Mozambique in Maputo, to provide grant aid of up to 2.076billion yen for the Project for the Construction of a Rural Water Supply Facility in Niassa Province. Under this project, people’s living environment in Niassa Province will improve through installing a rural water supply facility, which will allow access to safe and clean water. It is expected that this project will lead to reduction of waterborne diseases and nutritional improvement. Measures to combat climate change will also be conducted, and this project will contribute to the achievement of SDGs Goals 3, 6, and 13.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; access to services / acesso a serviços; climate change / mudanças climáticas; infrastructure / infrastrutura

Food security and livelihoods under a changing climate in Mozambique: preparing for the future - World Food Programme (World Food Programme, 2021)
Mozambique’s climate is characterized by relatively uniform temperatures across the country and a north-south rainfall gradient which results in higher more reliable rainfall amounts in the North, and lower more variable rainfall amounts in the South Historical climate analysis for the country shows that temperatures are already increasing and rainfall trends are dominated by year-to-year variability. Livelihoods and agricultural production systems are already being affected by the changing and more variable climate. Climate projections for the 2050s show strong agreement for an increase in temperature, but no strong trend for changes in rainfall. All scenarios of projected climate change will result in increased heat stress, reductions in water availability, and more frequent and intense extreme weather events, which could exacerbate food insecurity in the absence of adaptation.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas; security / segurança

LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

Policy analysis Food security, nutrition, climate change resilience, gender and the small-scale farmers Mozambique - Care; ActionAid (ActionAid and Care, 2017)
The analysis covers both national specific policies and those policies and commitments that the Government of Mozambique has signed as part of global collective efforts. The analysis aims to become a baseline to better understand the policy gaps and implementation challenges in in FNS and CCR towards women and smallholders in Mozambique. The main purpose of this analysis is to become useful source and instrument in the implementation of CARE Mozambique Advocacy Strategy, and also for the Government of Mozambique, donors and civil society organizations, to better identify the challenges for a more effective investment in gender transformative, climate resilient and nutrition smart agriculture.
Keywords: *snowball; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas